On the Klein–Gordon oscillator subject to a Coulomb-type potential - Bakke, K.; Furtado, C. (Annals of physics, 2015)
By introducing the scalar potential as modification in the mass term of the Klein–Gordon equation, the influence of a Coulomb-type potential on the Klein–Gordon oscillator is investigated. Relativistic bound states solutions are achieved to both attractive and repulsive Coulomb-type potentials and the arising of a quantum effect characterized by the dependence of angular frequency of the Klein–Gordon oscillator on the quantum numbers of the system is shown. •Interaction between the Klein–Gordon oscillator and a modified mass term.•Relativistic bound states for both attractive and repulsive Coulomb-type potentials.•Dependence of the Klein–Gordon oscillator frequency on the quantum numbers.•Relativistic analogue of a position-dependent mass system.